Physiological Traits and Growth Indicators Response of Triticale to Glutamic Acid Application Under Anbar Conditions. - Alhalbosi, Ahmed; ALobaidy, Bushra Sh. J (University of Thi-Qar Journal of agricultural research, 2025)
This study investigated the performance of various triticale cultivars and the impact of glutamic acid application on key physiological traits. We found significant differences among cultivars in nearly all measured parameters, underscoring the importance of genetic selection. Notably, Sara consistently excelled in vegetative growth, including plant height and flag leaf area, while Rizan demonstrated superior stomatal conductance, tillering capacity, and relative growth rate. Exogenous application of glutamic acid consistently improved plant performance across multiple traits. Specifically, a concentration of 500 mg L⁻¹ generally enhanced stomatal conductance, plant height, and tiller number, while 250 mg L⁻¹ was optimal for boosting relative growth rate and net photosynthesis. This underscores the importance of glutamic acid as an advantageous biostimulant. The study indicated strong connections between genetics and environment. The ideal reaction to glutamic acid was frequently particular to the cultivar. Sara and Rizan exhibited significant synergistic advantages from glutamic acid, frequently attaining optimal performance at certain dosages. Conversely, several cultivars demonstrated no enhancement or deterioration without optimum glutamic acid. In conclusion, to get the most out of triticale, you need to do two things: choose genetically better cultivars like Sara and Rizan and use glutamic acid at levels that are right for each cultivar and attribute you want. You need to use this focused method to get the most performance out of triticale in your area.